   Chapter 0.6, Problem 24E

Chapter
Section
Textbook Problem

Solve the equations in Exercises 1–26. 2 x − 3 x − 1 − 2 x + 3 x + 1 = 0

To determine

To calculate: The solution of the equation 2x3x12x+3x+1=0.

Explanation

Given information:

The equation, 2x3x12x+3x+1=0.

Formula used:

The FOIL method,

Step1: Take product of first terms.

Step2: Take product of outer terms.

Step3: Take product of the inner terms.

Step4: Take product of the last terms.

Step5: Add all the terms.

Calculation:

Consider the expression,

2x3x12x+3x+1=0

Rewrite the above expression as,

2x3x1=2x+3x+1

Multiplying both side of the above equation by (x+1)(x1),

2x3x1(x+1)(x1)=2x+3x+1(x+1)(x1)(2x3)(x+1)=(2x<

Still sussing out bartleby?

Check out a sample textbook solution.

See a sample solution

The Solution to Your Study Problems

Bartleby provides explanations to thousands of textbook problems written by our experts, many with advanced degrees!

Get Started

Calculate y'. 50. y=sin2(cossinx)

Calculus: Early Transcendentals

Find the derivative of the function. f(x)=5x+1

Single Variable Calculus: Early Transcendentals, Volume I

Convert the expressions in Exercises 8596 radical form. 94(1x)7/3

Finite Mathematics and Applied Calculus (MindTap Course List)

Factor: 27x354x

Elementary Technical Mathematics

Given: l1l2l3l4,AB=7,BC=5,CD=4,EF=6 Find: FG,GH,EH

Elementary Geometry For College Students, 7e

Multiply the following numbers and verify your answers. 4.

Contemporary Mathematics for Business & Consumers 